Loading dynamics of cold atoms into a hollow-core photonic crystal fiber - Wang, Yu (2021)
Cold atoms trapped and guided in hollow-core photonic crystal fibers provide a scalable diffraction-free setting for atom-light interactions for quantum technologies. However, due to the mismatch of the depth and spatial extension of the trapping potential from free space to the fiber, the number of cold atoms in the fiber is mainly determined by the loading process from free space to waveguide confinement. Here, we provide a numerical study of the loading dynamics of cold atoms into a hollow-core photonic crystal fiber. We use the Monte Carlo method to simulate the trajectories of an ensemble of cold atoms from free space trapping potential to optical potential inside a hollow-core fiber and calculate the temperature, loading efficiency, and geometry of the ensemble. We also study the noise sources that cause heating and a loss of atoms during the process. Our result could be used to design and optimize the loading process of cold atoms into a hollow-core fiber for cold atom experiments.